Faktor-Faktor yang Berhubungan dengan Stigma terhadap Penderita COVID-19 - Izzah Khoirunissa; Dhona Andhini; Sigit Purwanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the factors associated with the stigma against COVID-19 sufferers. The research design used an observational analytic research design with a cross-sectional approach. The results showed that the variables that were not associated with the stigma against COVID-19 sufferers were age (p=0.791), while the variables related to stigma against COVID-19 patients were gender (p=0.020), employment status (p=0, 0001), an education level (p=0.0001), knowledge level (p=0.0001), sources of information (p=0.0001), support from community leaders (p=0.0001), and support from health workers (p =0.0001). In conclusion, it is necessary to increase public knowledge, support community leaders, provide education about COVID-19 to the community, and be able to provide examples of good attitudes and behavior in treating COVID-19 sufferers and their families so that stigma does not occur again. Keywords: COVID-19 Sufferers, Stigma